AGRO-BIOLOGICAL ASSESSMENT OF RADISH ACCESSIONS AT NOVOSIBIRSK AREA - T. V. Steinert; A. V. Aliluev; L. M. Avdeenko (Овощи России, 2018)
The result of collaboration work between Siberian Research Institute of Plant Cultivation and Breeding, the branch of The Institute of Cytology and Genetics of the Siberian Branch of the Russian Academy of Sciences (ICG SB RAS) and the company OOO Geterozisnaya Selectia on ecological trial and assessment of economically valuable traits were obtained in promising radish accessions. The data on influence of sowing terms on yielding ability, formation of flower bearing stalks was analyzed and morphological descriptions for radish accessions were given. It was shown that the development of marketable radish roots can be possible in condition of long lasting light period. When sowing in the second decade of June less number of flower stalks formed on the plants than on the control plants of ‘Raniy Krasniy’. The sowing in the first decade of August did not give any plants with flower stalks in accessions 17-12 and 17-13. The highest yield at first sowing term was observed in accession 17-12 at second sowing term in accession 17-13, 5.6 and 6.1 kg/m2 respectively. The accession 17-12 was distinguished by root weight, 19.2 g. The highest dry matter content (5.31%) was observed in accession 17-11; the highest total sugar content (2.18%) was in accession 17-12; the highest ascorbic acid content (25.1 mg %) was in accession 17-13. The comparative analysis of data on summer and autumn sowing terms showed that when sowing in summer time, at long lasting light period the radish accessions were characterized by the more number of plants with flower stalks; more developed leaf apparatus; larger roots and enriched biochemical composition as compared with the accessions sown in autumn time. All accessions tested belonged to early-maturing group, where the root formation takes for 22-25 days. For economically valuable traits the accessions 17-12 and 17-13 were selected out.